The Interrelation Between Military Discipline Infraction and Military Criminal Charge in Indonesia - Amalia, Regita Wienda; Anditya, Ariesta Wibisono (Nurani Hukum, 2024)
Violations of the Military Discipline Law that culminate in a disciplinary tribunal’s decision possess only minimal binding force. In other words, the tribunal’s ruling merely serves as a recommendation to the superior vested with punitive authority (atasan yang berhak menghukum, abbreviated as Ankum). If it subsequently emerges that an incident threatens the integrity of a military unit, the Ankum is entitled to invoke a higher level of legal authority by referring the matter to a military criminal court. In narcotics cases committed by military personnel that are initially deemed disciplinary infractions, the Ankum may subsequently refer the matter to the Military Police (Polisi Militer, legally abbreviated as POM) for further military criminal proceedings. This study constitutes doctrinal legal research supported by data drawn from the literature. To address the research questions, a legal-literature-review approach was adopted. The findings indicate that violations of Indonesian military disciplinary law may escalate into military criminal offenses through the decision-making process of the Ankum.